2017
DOI: 10.1002/adem.201600674
|View full text |Cite
|
Sign up to set email alerts
|

Phase Decomposition of a Single‐Phase AlTiVNb High‐Entropy Alloy after Severe Plastic Deformation and Annealing

Abstract: An equiatomic AlTiVNb high-entropy alloy is deformed by high pressure torsion inducing a nanocrystalline microstructure. The samples then are subjected to isochronal heat treatments between 300 C and 1000 C. The hardness increase from %7.4 GPa for the as-processed state to 10.4 GPa for an annealing temperature of 700 C, while for higher temperatures the hardness starts to decrease. Furthermore, the reduced modulus increases after annealing treatments as well. It will be shown that the unusual annealing respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 54 publications
2
17
0
1
Order By: Relevance
“…The transformation between solid‐solution phase and intermetallic‐compound phase can be achieved by heat treatment. Schuh et al found that the internal friction and defect structure of equiatomic AlTiVNb nanocrystalline HEA were reduced under the annealing treatment, making the reduced modulus close to the modulus of coarse grains 111. Once the modulus getting closed to saturation, the HEA began to form intermetallic‐compound phase.…”
Section: Phase Engineering Of Heasmentioning
confidence: 99%
See 1 more Smart Citation
“…The transformation between solid‐solution phase and intermetallic‐compound phase can be achieved by heat treatment. Schuh et al found that the internal friction and defect structure of equiatomic AlTiVNb nanocrystalline HEA were reduced under the annealing treatment, making the reduced modulus close to the modulus of coarse grains 111. Once the modulus getting closed to saturation, the HEA began to form intermetallic‐compound phase.…”
Section: Phase Engineering Of Heasmentioning
confidence: 99%
“…Schuh et al found that the internal friction and defect structure of equiatomic AlTiVNb nanocrystalline HEA were reduced under the annealing treatment, making the reduced modulus close to the modulus of coarse grains. [111] Once the modulus getting closed to saturation, the HEA began to form intermetalliccompound phase. Similarly, Dai et al found that the abundant grain boundaries in nanocrystalline HEA provided a pathway for the rapid diffusion of elements along the grain boundary at a low-temperature annealing condition.…”
Section: Temperature Controllingmentioning
confidence: 99%
“…Compared with 3d transition HEAs, the grain sizes that can be achieved in these alloys are much larger, typically in the range of 40-50 nm. Processing via HPT does not affect this average grain size range and has been used to produce singlephase BCC HEAs by Schuh et al [42,43].…”
Section: Materials For Nc Heasmentioning
confidence: 99%
“…An abundance of investigations have emerged in the literature focusing on microstructural characteristics, defect evolution as well as mechanical properties for HEAs after SPD. [99][100][101][102][103][104][105][106][107][108][109] A recent work by Bhattacharjee et al 106 reported that the nanolamellar AlCoCrFeNi 2.1 HEA, which was achieved by cryorolling and annealing processes, exhibited a remarkable increase in both the yield strength and the ultimate tensile strength (UTS) without sacrificing too much ductility [ Fig. 8(a)].…”
Section: Grain Coarseningmentioning
confidence: 99%